Physical and Organoleptic Characteristics of Cowpea Yogurt (Vigna unguiculata L.) with the Addition of Roselle Flower Extract (Hibiscus sabdariffa L.) - Ika Dyah Kumalasari; Aisyah Putri Muharami; Wahidah Mahanani Rahayu (JST (Jurnal Sains dan Teknologi), 2026)
Yoghurt is not only produced from cow’s milk, but can also be made from high protein plant based ingredients such as legumes, one of which is cowpea. However, cowpea has a disadvantage in the form of a bitter and unpleasant aroma and taste caused by lipoxygenase enzyme activity. These undesirable characteristics could be reduced by combining cowpea with other food ingredients. The addition of dates as a natural sweetener and rosella flower extract, which has a distinctive fragrance and refreshing sour taste, was expected to improve the physical and organoleptic properties of cowpea yoghurt. The purpose of this study was to determine the physical and organoleptic characteristics of cowpea yoghurt with the addition of rosella flower extract. This study used four formulations of cowpea milk with different concentrations of rosella flower extract, namely F0 (100%:0%), F1 (98%:2%), F2 (96%:4%), and F3 (94%:6%), each formulation was added with 30 g of date juice as a natural sweetener. The study was conducted in four stages, including yoghurt production, viscosity testing, product acceptance testing (scoring), and organoleptic testing (hedonic and descriptive). The results showed that rosella flower extract significantly affected the viscosity and organoleptic acceptance of cowpea yoghurt. Viscosity values and hedonic test showed significant effects (p<0.05) on colour, aroma, thickness, texture, taste, and overall acceptance. Formulation F3 was the most preferred, while F0 showed the highest viscosity value. Yoghurt F3 showed dark brown colour, soft texture, moderate thickness, sour-sweet taste. Roselle flower extract improved the physical and organoleptic characteristics of jackfruit yoghurt.